Nutrition Counseling Effect Using Comic on Knowledge and Attitudes of Girls About 1000 First Days of Life in Preventing Stunting in Percut Sei Tuan 1 Senior High School - Erlina Nasution; Ardiana Batubara; Putri Nurhidayah; Fitriyani Pulungan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Stunting is a growth disorder in children caused by poor nutritional intake, repeated infections and inadequate psychosocial stimulation. These nutritional problems will occur if the nutrients are not fulfilled in the period of First Thousand Days of Life. Objective: to determine the effect of nutrition counseling using comic media on the knowledge and attitudes of girl adolescent about 1000 first days of life in preventing stunting at SMAN 1 Percut Sei Tuan. Methods: This type of research was Pre-Experimental with the One Group Pre-Post Test research design which only used the experimental group without a control/comparison group. The population in this study were all class XI teenage girls who were at SMAN 1 Percut Sei Tuan in 2023, namely 121 people. Data collection was carried out by interviews using questionnaires and analysis using the T-dependent test. Results: This study showed the effect of nutritional counseling using comic media on knowledge (p=0.000) and attitudes (p=0.000) in preventing stunting at SMAN 1 Percut Sei Tuan. Conclusion: There is an increase in knowledge and attitudes of young women after being given nutritional counseling using comic media.